Ongoing removals of invasive lionfish in Honduras and their effect on native Caribbean prey fishes - Peiffer, Friederike; Bejarano, Sonia; Palavicini de Witte, Giacomo; Wild, Christian (PeerJ, 2017)
The invasion of Indo-Pacific lionfish is one of the most pressing concerns in the context of coral reef conservation throughout the Caribbean. Invasive lionfish threaten Caribbean fish communities by feeding on a wide range of native prey species, some of which have high ecological and economic value. In Roatan (Honduras) a local non-governmental organisation (i.e. Roatan Marine Park) trains residents and tourists in the use of spears to remove invasive lionfish. Here, we assess the effectiveness of local removal efforts in reducing lionfish populations. We ask whether reefs subject to relatively frequent removals support more diverse and abundant native fish assemblages compared to sites were no removals take place. Lionfish biomass, as well as density and diversity of native prey species were quantified on reefs subject to regular and no removal efforts. Reefs subject to regular lionfish removals (two to three removals month−1) with a mean catch per unit effort of 2.76 ± 1.72 lionfish fisher−1 h−1 had 95% lower lionfish biomass compared to non-removal sites. Sites subject to lionfish removals supported 30% higher densities of native prey-sized fishes compared to sites subject to no removal efforts. We found no evidence that species richness and diversity of native fish communities differ between removal and non-removal sites. We conclude that opportunistic voluntary removals are an effective management intervention to reduce lionfish populations locally and might alleviate negative impacts of lionfish predation. We recommend that local management and the diving industry cooperate to cost-effectively extend the spatial scale at which removal regimes are currently sustained.
Keywords: Invasive lionfish; Population control; Removal effort; Native prey fish; Roatan; Caribbean